Cystatin C is associated with poor survival in amyotrophic lateral sclerosis patients - Jiang, Qirui; Guo, Yuan; Yang, Tianmi; Li, Shirong; Hou, Yanbing; Lin, Junyu; Xiao, Yi; Ou, Ruwei; Wei, Qianqian; Shang, Huifang (Frontiers in Neuroscience, 2024)
Background: Cystatin C (CysC) levels in amyotrophic lateral sclerosis (ALS) have been found changes, however, the associations between serum CysC levels and the progression and survival of ALS remain largely unknown.: A total of 1086 ALS patients and 1026 sex-age matched healthy controls (HCs) were enrolled in this study. Serum CysC, other renal function, and metabolic parameters were measured. Correlation analysis and binary logistic regression were used to explore the factors related to serum CysC. Kaplan-Meier curve and Cox regression model were used for survival analysis.Results: CysC levels were significantly higher in ALS patients compared to HCs (0.94 vs 0.85mg/L, p<0.001). Compared with ALS patients with lower CysC levels, those with higher CysC levels had an older age of onset, significantly lower ALSFRS-R scores (40.1 vs. 41.3, p<0.001), a faster disease progression rate (0.75 vs. 0.67, p=0.011), and lower frontal lobe function scores (15.8 vs. 16.1, p=0.020). In the correlation analysis, CysC levels were significantly negatively correlated with ALSFRS-R scores (r=-0.16, p<0.001). Additionally, ALS patients with higher CysC levels had significantly shorter survival time (40.0 vs. 51.8, p<0.001) compared to patients with lower CysC levels. Higher CysC levels were associated with a higher risk of death in Cox analysis (HR: 1.204, 95% CI: 1.012-1.433). However, when treatment was included in the model, the result was no longer significant.Conclusions: CysC levels in ALS patients were higher compared to HCs. Higher CysC levels were associated with greater disease severity, faster progression rate and shorter survival, needing early intervention.